2014
DOI: 10.5001/omj.2014.24
|View full text |Cite
|
Sign up to set email alerts
|

Does Spinal Analgesia have Advantage over General Anesthesia for Achieving Success in In-Vitro Fertilization?

Abstract: According to analysis of recorded data in an infertility treatment center in Iran, it is recommended to use spinal anesthesia instead of general anesthesia for oocyte retrieval to achieve successful in-vitro fertilization outcome. This can be studied and investigated further via a proper multicentric study in the country.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Recent trials concluded that the use of spinal anesthesia improves IVF outcome [ 1 , 2 ]. Spinal anesthesia increased significantly the chance of IVF success in a randomized prospective trial by Azmude et al in 2013 [ 1 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent trials concluded that the use of spinal anesthesia improves IVF outcome [ 1 , 2 ]. Spinal anesthesia increased significantly the chance of IVF success in a randomized prospective trial by Azmude et al in 2013 [ 1 ].…”
Section: Resultsmentioning
confidence: 99%
“…Spinal anesthesia increased significantly the chance of IVF success in a randomized prospective trial by Azmude et al in 2013 [ 1 ]. According to a cohort study based on analysis of patient records at Mirza Kochak Khan Hospital, Tehran University of Medical Sciences (Aghaamoo et al, 2014), it was recommended to use spinal anesthesia instead of GA for oocyte retrieval, to achieve successful in vitro fertilization outcome [ 2 ]. Nerve blocks (ovarian block and paracervical block) as an additional method for pain relief proved no harm on the IVF success [ 3 , 4 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there have been fewer studies related to inhalation agents, it has been reported that halotane and isoflurane in particular have harmful effects on oocytes through the transfer of follicular fluid. However, it should be noted that they were animal studies and the surgical procedures applied were lengthy laparoscopic OPU methods [18][19][20]. Piroli et al reported similar high rates of fertilisation using general anaesthesia with sevoflurane and with local anaesthesia methods in transvaginal OPU procedure [21].…”
Section: Discussionmentioning
confidence: 99%
“…The procedure necessitates a short-acting anesthetic approach with minimal side-effects. The various anesthetic modalities used for transvaginal oocyte retrieval include monitored anesthesia care, conscious sedation, general anesthesia, regional anesthesia, local injection as a paracervical block, epidural block, subarachnoid block, total intravenous anesthesia, patient-controlled analgesia, and acupuncture [4,5,6].…”
Section: Introductionmentioning
confidence: 99%